2015
DOI: 10.1177/1933719114542021
|View full text |Cite
|
Sign up to set email alerts
|

Sox2 Gene Amplification Significantly Impacts Overall Survival in Serous Epithelial Ovarian Cancer

Abstract: Epithelial ovarian cancer (EOC) is the deadliest gynecologic cancer. Recently, the existence of ovarian cancer stem cells has been reported. Sox2, Nanog and Oct4 are key markers of ''stemness''. The objective of this study was to determine whether Sox2, Nanog, and Oct4 are associated with EOC and poor outcome. The expression of these markers was assessed by immunofluorescence staining and real-time RT-PCR in human EOC cell lines MDAH-2774 and SKOV-3, while the cancer genome atlas (TCGA) dataset was analyzed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 80 publications
(113 reference statements)
3
27
0
Order By: Relevance
“…We investigated whether current clinical data in the TCGA database could corroborate this finding and we found that indeed, SOX2, but not OCT4 or NANOG, is significantly higher in tumors that were recurrent. These data are also in alignment with other studies showing that SOX2 is associated with worse overall survival of serous epithelial ovarian cancer [54][55][56]. Although additional studies are required to confirm SOX2 as a bona-fide TIC marker, our data confirms previous studies establishing SOX2 in spheroid formation and tumor initiation [19,24] and indicates SOX2 is strongly correlated with a TIC phenotype and may serve as a more reliable marker of ovarian TICS with high relapse potential.…”
Section: Discussionsupporting
confidence: 91%
“…We investigated whether current clinical data in the TCGA database could corroborate this finding and we found that indeed, SOX2, but not OCT4 or NANOG, is significantly higher in tumors that were recurrent. These data are also in alignment with other studies showing that SOX2 is associated with worse overall survival of serous epithelial ovarian cancer [54][55][56]. Although additional studies are required to confirm SOX2 as a bona-fide TIC marker, our data confirms previous studies establishing SOX2 in spheroid formation and tumor initiation [19,24] and indicates SOX2 is strongly correlated with a TIC phenotype and may serve as a more reliable marker of ovarian TICS with high relapse potential.…”
Section: Discussionsupporting
confidence: 91%
“…Knockdown of SOX2 in cell lines accordingly decreased chemoresistance to cisplatin via down-regulating expression of ABCB1 , ABCG2 , and ABCC6 31 . These results were accordance with those of researches on the roles of SOX2 based on OC cell lines, but not with researches based on patients’ samples in other cases 9,31,34,38,39 . Further simultaneous in vitro and in vivo researches into SOX2 are therefore needed to develop its role as a promising new therapeutic target for patients with OC.…”
Section: Sox Genes In Gcssupporting
confidence: 69%
“…On the other hand, Pham et al 38 demonstrated that high expression level of SOX2 was a favorable biomarker indicating longer DFS and overall survival (OS) in patients with stage II–IV high-grade serous OC among 215 cases of OC. Other researchers also affirmed the good prognostic effects of SOX2 in 570 samples from patients with ovarian serous cystadenocarcinoma 39 . The mechanisms responsible for these different effects of SOX2 may be due to various factors, such as feedback mechanisms of SOX2 expression, interactions between SOX2 in the cytoplasm and nucleus, or differences between patient spectra and measuring methods.…”
Section: Sox Genes In Gcsmentioning
confidence: 83%
“…In this regard, the SOX2 gene is amplified in several cancers, [41, 5456] and high levels of SOX2 correlate with poor prognosis in many cancers [24, 5760]. As shown previously, SOX2 protein levels vary considerably between different PDAC cell lines [23].…”
Section: Discussionmentioning
confidence: 77%